Timing of innovation policies when carbon emissions are restricted: an applied general equilibrium analysis - Tom-Reiel Heggedal; Karl Jacobsen (Statistics Norway, Research Department, 2008)
This paper studies the timing of subsidies for environmental research and development (R&D) and how innovation policy is influenced by the costs of emissions. We use a dynamic computable general equilibrium (CGE) model with both general R&D and specific environmental R&D. We find two results that are important when subsidizing environmental R&D in order to target inefficiencies in the research markets. Firstly, the welfare gain from subsidies is larger when the costs of emissions are higher. This is because a high carbon tax increases the social (efficient) investment in environmental R&D, in excess of the private investment in R&D. Secondly, the welfare gain is greater when there is a falling time profile of the rate of subsidies for environmental R&D, rather than a constant or increasing profile. The reason is that the innovation externalities are larger in early periods.
Keywords: E62; H31; O38; Q55; 330; Applied general equilibrium; endogenous growth; research and development; carbon emissions.